Peniadaan Salat Jumat dalam Surat Edaran Gubernur Sulsel Nomor: 451.11/2057/2020 Selama Pandemi Covid-19 Perspektif MaqÄá¹£id al-SyarÄ«ah - Sirajuddin, Sirajuddin; Kasjim Salenda; Abdul Wahid Haddade (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2020)
This research aimed to analyze the relevance of dismissal of friday prayers in circular letter of south sulawesi governor number: 451.11 / 2057/2020 during covid-19 pandemic from the perspective of maqÄá¹£id al-syarÄ«â€™ah. This research is library research using a qualitative approach and content analysis techniques. The results of the research conclude that the substance of the circular letter is relevant to the principle of maqÄá¹£id al-syarÄ«â€™ah which is the core philosophy of the formation of Islamic law in presenting the benefit of mankind in the world and the hereafter, both from the aspect of maqÄá¹£id al-kulliyyah (universal) and maqÄá¹£id al-juz'iyyah (partial) especially maqÄá¹£id in obeying a leader. Therefore, the emergence of the phenomenon of counter attitudes from some people and even preachers towards the policy should not occur.